Molecular evaluation of ribosomal protein L9 and lipoic acid synthetase genes and in lung and apoptosis - Mphahlele, Raesibe Paulinah (My University, 2012)
Background: A human ribosomal protein L9 (RPL9) encodes a protein that is a component of the 60S subunit. RPL9 is located on chromosome 4p14 and is approximately 5.5 kb in length and contains 8 exons. The message for human RPL9 is 712 nucleotides long. Some of the functions of RPL9 documented so far include the crucial involvement of the gene product in cell proliferation and protein biosynthesis. Lipoic acid synthetase (LIAS) is a 1.73 kb gene also located at chromosome 4p14. Alternative splicing occurs at these locus and two transcript variants encoding distinct isoforms have been identified but in this study the results represents both isoforms together. The protein encoded by LIAS gene belongs to the biotin and lipoic acid synthetases family and localizes in the mitochondrion. Function of lipoic acid synthetase is not yet well documented. Some studies have attempted to characterise its function by looking at the biological pathways at which LIAS gene product plays a crucial role, for example the biosynthesis of alpha-lipoic acid. Alpha lipoic acid is a natural antioxidant and it is also naturally-occurring enzyme co-factor found in a number of multi-enzyme complexes regulating oxidative metabolism. Motivation for study: RPL9 and LIAS were previously found to be mutated in CHO (Chinese Hamster Ovary) cell lines and these mutant lines had gained resistance to apoptosis. Aim: The main objective of this study was to evaluate the expression pattern of RPL9 and LIAS in lung cancer and to characterise their role in apoptosis and also to determine if the expression pattern of this genes varies between normal and diseased state of the tissue. Methods: In Situ hybridization, quantitative Real Time PCR, TUNEL and Bio-informatics have been employed in order to attain the objectives of this study. Results: In Situ hybridization showed that RPL9 localises in the cytoplasm and it is up-regulated in lung cancer relative to normal lung. LIAS localises in the cytoplasm and it is also up-regulated in lung cancer. The expression of RPL9 was relatively higher than that of LIAS determined by the intensity of localisation. Quantitative real time PCR confirmed the up-regulation of RPL9 and LIAS in lung cancer. RPL9 and LIAS were found to be up-regulated 8 and 4 fold respectively in lung A549 lung adenocarcinoma relative to MRC5 normal lung fibroblast cell lines. TUNEL showed the highest DNA fragmentation in adenocarcinoma, followed by squamous cell lung carcinoma then large cell lung carcinoma which is the same pattern observed in RPL9 and LIAS mRNA localisation by In Situ hybridization. To further characterise the role of RPL9 and LIAS in human, Bio-informatics tools were used and the results revealed that RPL9 is highly conserved through evolution, up-to 100 % identical to chimpanzee and 98 % to mouse. LIAS was found to be 91 % identical to rat and 90 % identical to mouse. It has been documented that the rate of conservation of a gene in evolution is believed to be correlated with its biological importance and its number of protein–protein interactions. Conclusion: All these discoveries coupled with resistance to apoptosis of CHO cell line in which RPL9 and LIAS were found to be mutated following promoter-trap mutagenesis, strongly suggests that RPL9 might be playing a role in cell cycle and apoptosis. RPL9 has been highly conserved through evolution. Manipulation of this gene can lead to greater biological discoveries in cancer research and the elevated expression of RPL9 can be used as a molecular marker for early detection of cancer.
Keywords: Lungs - Cancer.; Proteins; Apoptosis.